MY TENT IS MY FORTRESS – A vadkempingezés változása a Tisza-tó térségében - Czicze, Gábor; Benkhard, Borbála Rita (Acta Carolus Robertus, 2020)
The large reservoir of Tisza-tó (sometimes-called Tisza Lake) was born in the second half of 20th century and today defined as individual priority tourism development area. The diverse nature-like landscape is the main attraction, offering a variety of opportunities for sport fishing activities too. The reservoir can be fished by different methods throughout the year, and facilities and fish populations are constantly being developed. Due to the sport fishing habits the anglers use to spend all the nights or longer period at the water, although camp activity is prohibited almost on the whole area. In 2001, a wilderness camp survey was carried out as part of a thesis at the University of Debrecen, but according to the operators of the area, littering is still one of the biggest problems on the banks of the reservoir. We have therefore set a goal to repeat and expand the survey in the context of thesis research. In the summer of 2019, we completed the mapping of the entire Tisza-tó reservoir, on water and land. In doing so, a field form and photo documentation was completed at each location. The geographic coordinates, the area affected by illegal camping, type of the constructions, fire pits, the rests and amounts of waste were recorded in to our database about the whole area. By processing the data, we will explore the current situation, allow comparison of each pool and analyse the relationship between the points involved in wildlife camping with legal infrastructure. On the other hand, compared to the maps of the previous survey can be followed the changes in the last 20 years. In this paper, we present several results of this research. Based on it, illegal camping and littering have decreased overall. However, despite infrastructural improvements and management measures to promote good behaviour, much less than expected.